Curcumina protege da cistite hemorrágica induzida por ifosfamida mediante inibição da expressão de E-selectina e da migração de neutrófilos - Silva, Francisco Wanderlei Lima (2017)
Hemorrhagic cystitis (HC) is an inflammatory process of the urinary bladder, characterized by mucosal injury, hematuria, dysuria, increased urinary frequency and urgency, as well as severe pelvic pain. Oxazaphosphorine-based chemotherapy, including cyclophosphamide and ifosfamide (IFO), is one main cause of CH. Despite advances in CH management, administration of higher doses of these drugs, such as in preconditioning for bone marrow transplantation, HC remains a serious clinical problem. Curcumin is the component of Curcuma longa rhizomes, which has biological interest for its anti-inflammatory and anticancer properties. In the present research, the protective effect of curcumin was evaluated on hemorrhagic cystitis induced by ifosfamide. Methods: Swiss male mice (20-25 g) were treated by oral administration with vehicle (0.9% saline, tween 80 and 70% alcohol) or curcumin (10, 30 and 100 mg/kg) 1h before and 6h after induction of CH with IFO (400 mg / kg, ip). Following 12h of HC induction, the mice were euthanized for bladder excision. Macroscopic damage, vascular permeability, myeloperoxidase, histopathological injury, cytokine levels, and E-selectin immunostaining were measured. ANOVA/Bonferroni or Kruskal-Wallis/Dunn's test were used for statistical analysis. p<0.05 was accepted as significant. Results: Curcumin attenuated edema and hemorrhage scores at doses of 10, 30 and 100 mg/kg (p<0.05) when compared to the IFO group. Curcumin at the dose of 30 mg/kg also reduced bladder wet weight (p<0.05 vs IFO). The histopathological analysis showed that the IFO promoted edema, hemorrhage, and urothelial damage, and this injury was significantly prevented by curcumin, as detected by preserved urothelial and muscle layer, as well as absence of edema and hemorrhage. In addition, curcumin attenuated neutrophil accumulation into the bladder. Conversely, IFO-related increased levels of KC (keratinocyte chemokine, a murine analogue of the human chemokine IL-8) and interleukin-1 (IL-1) in the bladders were not prevented by curcumin (30mg/kg). On the other hand, there was a significant reduction in the immunoexpression of E-selectin in curcumin-administered group. Conclusion: Curcumin has anti-inflammatory activity in HC due to the inhibition of neutrophil migration probably by reduction of E-selectin expression.